2021
DOI: 10.3390/biom11040565
|View full text |Cite
|
Sign up to set email alerts
|

A New Era of Neuro-Oncology Research Pioneered by Multi-Omics Analysis and Machine Learning

Abstract: Although the incidence of central nervous system (CNS) cancers is not high, it significantly reduces a patient’s quality of life and results in high mortality rates. A low incidence also means a low number of cases, which in turn means a low amount of information. To compensate, researchers have tried to increase the amount of information available from a single test using high-throughput technologies. This approach, referred to as single-omics analysis, has only been partially successful as one type of data m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Using central nervous system (CNS) tumours as an example, multi-omic data, including single-nucleotide polymorphism (SNP) mutations (e.g., TARDBP), gene methylation (e.g., 64-MMP) and transcriptome abnormalities (e.g., miRNA-21), are known to predict the progression of meningiomas [76]. A systematic review of multi-omic glioblastoma studies by Takahashi et al found that most utilised ML techniques for analysis, likely due to the size and complexity of the data [77]. In one study of 156 patients with oligodendrogliomas, mRNA expression arrays, microRNA sequencing and DNA methylation arrays were analysed using a multi-omics approach to better classify 1p/19q co-deleted tumours [78].…”
Section: Data Types: Multi-omic Datamentioning
confidence: 99%
“…Using central nervous system (CNS) tumours as an example, multi-omic data, including single-nucleotide polymorphism (SNP) mutations (e.g., TARDBP), gene methylation (e.g., 64-MMP) and transcriptome abnormalities (e.g., miRNA-21), are known to predict the progression of meningiomas [76]. A systematic review of multi-omic glioblastoma studies by Takahashi et al found that most utilised ML techniques for analysis, likely due to the size and complexity of the data [77]. In one study of 156 patients with oligodendrogliomas, mRNA expression arrays, microRNA sequencing and DNA methylation arrays were analysed using a multi-omics approach to better classify 1p/19q co-deleted tumours [78].…”
Section: Data Types: Multi-omic Datamentioning
confidence: 99%
“…In addition, recently, traces of the entry of ML into the field of multi-omics data analysis from neuro-oncology research have been seen. So that the application of this advanced technology in various fields of cancer is getting more colorful and effective (Takahashi et al, 2021).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Along with radiomics, genomics, transcriptomics, and high-throughput proteomics are all examples of “omics” techniques that provide data for the examination of molecular constituents. In a general sense, the multi-omics analysis consists of three components: input data, technique, and output data ( 162 ). Multiple omics analysis is crucial in neuro-oncology research with limited sample sizes.…”
Section: Limitations and Future Considerationsmentioning
confidence: 99%